Reduction Cost in Material Spring-type Coil for Heavy-duty Oil Filter By-pass System with Redesigning - Adam Satria; Edwin Sahrial Solih; Sanurya Putri Purbaningrum; Abdul Wahid Arohman; Ridho Hans Gurning (P3M Politeknik Negeri Cilacap, 2025)
The bypass system in oil filters plays a crucial role in maintaining engine cleanliness and performance by allowing oil to flow through the filter when the pressure exceeds set limits. A critical component of this system is the coil spring that controls the bypass valve. In this study, an experimental approach was applied to reduce material cost while preserving performance. We redesigned the spring from four coils of 3.5 mm diameter to three coils of 3 mm diameter, using the same standard hard steel wire SW‑C. The redesigned springs were subjected to a standard impulse test of 250,000 cycles under 7 kgf/cm² pressure and a loading test with deflections from 1 to 10 mm at pressures up to 11 kgf. Results show that the new three‑coil SW‑C spring meets all performance criteria: impulse life and load‑deflection characteristics fall within standard tolerances. A direct comparison with the original design demonstrates negligible differences in functional behavior, confirming that material usage and costs can be reduced without sacrificing reliability. These findings offer valuable guidance for the cost‑efficient production of oil filter components in automotive engineering.